ANALISIS DISPOSISI MATEMATIKA BERDASARKAN HIGHER ORDER THINKING TAKSONOMI BLOOM (Studi Kasus Mahasiswa Pendidikan Matematika Universitas Muhammadiyah Cirebon) - Desy Lusiyana; S Sumliyah (Phenomenon : Jurnal Pendidikan MIPA, 2018)
Mathematical dispositions should be considered in the learning process. The purpose of this study is to determine the disposition possessed by students in thinking of Higher Order Thinking (HOT). The mathematical disposition studied is the student's high-order thinking mathematical disposition, so knowing students' attitudes and levels makes it easy for educators to make learning tools both teaching materials, teaching aids, and appropriate and meaningful methods. The method used in this study is qualitative and quantitative. Data collection is used namely tests and questionnaires. Based on the analysis obtained sig 1.6%. The results of data analysis showed that there were differences in mathematical dispositions based on students' level of thinking based on HOT and a more dominant mathematical disposition, namely self-confidence and role appreciation. So that it can be concluded that the higher the level of thinking of students, the more mathematical dispositions they have.